Drug-induced hepatitis, drug-induced autoimmunity or classical autoimmune hepatitis: How can we differentiate ? - Dilek OĞUZ; Engin ALTINTAŞ; Sabite KACAR; Yasemin ÖZDERİN ÖZİN and Orhan SEZGİN and Neslihan İNCİ ZENGİN (Turkish Journal of Gastroenterology, 2019)
-